Masalah sosial dan upaya pemecahannya - Soetomo, 1946- (Yogyakarta : Pustaka Pelajar, 2008)
Issues on social problem and its solution in Indonesia.
Includes bibliographical references (p. 399-407) and index.
Keywords: Social problems -- Indonesia; Indonesia -- Social policy; Indonesia -- Social conditions